Evaluating Sensory Quality of Instant Noodles Colored with Carbonized Black Glutinous Rice Straw - Rahayu, Lisa Fitri; Murtini, Erni Sofia (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This study investigated the sensory impact of incorporating a liquid black colourant derived from black glutinous rice straw carbon into instant noodles. The colourant was formulated by dispersing fine carbon in fructose syrup and processed through sonication to enhance stability, then added to noodle dough at concentrations ranging from 0% to 6%. A sensory evaluation was conducted with 25 untrained panellists, who assessed colour, aroma, taste, texture, and overall acceptability using a nine-point hedonic scale. Results showed that the 4% concentration achieved the highest sensory scores, offering an appealing colour, a pleasant aroma, a good taste, and a consistent texture. Higher concentrations reduced acceptability due to off-flavor and aroma. These findings support the use of carbonised rice straw as a sustainable, natural colourant in instant noodle production. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action